Ways And Stages of Speech Development of Primary School Students - Quvonov Zahriddin Quvonovich (Genius Publishing Group, 2022)
This article discusses the theoretical and methodological foundations for the development of speech in elementary school students. Based on pedagogical data, the author analyzed the problem and studied and systematized the ways and stages of the development of students' speech.
Keywords: Students; Primary Education; Teacher; Speech